Polymeric coagulant as well as preparation method and application thereof
By preparing a polymeric coagulant, combining liquid polymer aluminum chloride, dimethyldiallyl ammonium chloride copolymer, chitosan-porous carbon nanomaterials and quaternary ammonium salt modified bentonite, the existing mixture is solved The deficiencies in the pollutant removal effect of coagulants have achieved efficient removal of COD and suspended substances in a variety of wastewater.
Patent Information
- Application Number
- CN202411707654.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
The existing coagulants have shortcomings in the pollutant removal effect, especially the flocculation ability of inorganic coagulants is poor, while the single use of organic coagulants is not good, and different types of organic flocculants need to be selected according to the nature of the wastewater.
Using a polymeric coagulant, the preparation method comprises performing a first polymerization reaction of liquid polymeric aluminum chloride, dimethyldiallyl ammonium chloride copolymer and a partial initiator, followed by chitosan-porous carbon nanometers The material, quaternary ammonium modified bentonite and the residual initiator undergo a second polymerization reaction to form a polymerized coagulant with high efficiency pollutant removal ability.
It has achieved the effect of small amount of addition and high pollutant removal rate. It is suitable for the treatment of a variety of wastewater, including sludge discharge water, garbage leachate and domestic sewage, and the COD and suspended removal rates are both high.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a polymeric coagulant and a preparation method and application thereof. Background Art
[0002] Coagulation is a commonly used water treatment method. By adding coagulants, suspended matter or colloidal particles in wastewater can be aggregated to form larger precipitates or gel systems, which are convenient for separation from water, thereby achieving the removal of tiny suspended matter and colloidal particles.
[0003] At present, coagulants are divided into inorganic coagulants and organic coagulants. Inorganic coagulants mainly include traditional aluminum and iron coagulants, such as aluminum sulfate, polyaluminum chloride, ferric chloride, polyferric sulfate, etc. Organic coagulants can be divided into synthetic and natural types. Synthetic types include sodium polyacrylate, sodium carboxymethyl cellulose, etc., and natural types include starch, protein, etc. Inorganic flocculants are cheap, but have poor flocculation ability and are not ideal for pollutant removal. Organic flocculants are added in small amounts and react quickly, but the effect of single use is poor, and different types of organic flocculants usually need to be selected according to the nature of the sewage.
[0004] In summary, there is an urgent need to develop a coagulant with low addition amount, high pollutant removal rate and applicable to a variety of wastewaters. Summary of the invention
[0005] In view of this, the present invention provides a polymeric coagulant and a preparation method and application thereof. The polymeric flocculant provided by the present invention fully combines the advantages of organic and inorganic flocculants, has a small addition amount, a high pollutant removal rate, and is applicable to a variety of wastewaters.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a polymeric coagulant comprises the following steps:
[0008] Mixing liquid polyaluminium chloride, dimethyldiallylammonium chloride copolymer and part of initiator to carry out a first polymerization reaction to obtain a reaction liquid;
[0009] The reaction solution, chitosan-porous carbon nanomaterial, quaternary ammonium salt-modified bentonite and the remaining part of the initiator are mixed to carry out a second polymerization reaction to obtain the polymerization coagulant.
[0010] Preferably, the usage ratio of the liquid polyaluminium chloride and the dimethyldiallylammonium chloride copolymer is (100-300) mL: (2-10) g.
[0011] Preferably, the preparation method of the chitosan-porous carbon nanomaterial comprises the following steps: mixing chitosan, porous carbon, water and an alkaline reagent for composite reaction to obtain the chitosan-porous carbon nanomaterial;
[0012] The mass ratio of chitosan to porous carbon is 1:(1-3); the alkaline reagent is ammonia water, and the mass fraction of ammonia water is 15%-40%; the pH value of the composite reaction is 8-9; the temperature of the composite reaction is 60-80°C, and the reaction time is 1-2h.
[0013] Preferably, the preparation method of the quaternary ammonium salt modified bentonite comprises the following steps: mixing a quaternary ammonium salt solution and bentonite and then drying to obtain the quaternary ammonium salt modified bentonite; the mixing temperature is 45-70°C and the time is 1-2h; the drying temperature is 100-120°C.
[0014] Preferably, the concentration of the quaternary ammonium salt solution is 1wt% to 7wt%; the dosage ratio of the quaternary ammonium salt solution to bentonite is (2 to 6) mL: (1 to 2) g; the quaternary ammonium salt in the quaternary ammonium salt solution is a long-chain alkyl ammonium bromide; and the number of carbon atoms of the long-chain alkyl in the long-chain alkyl ammonium bromide is 16.
[0015] Preferably, the long-chain alkyl ammonium bromide includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium bromide, cetyltriethylammonium bromide and cetyltributylammonium bromide.
[0016] Preferably, the usage ratio of the liquid polyaluminium chloride, chitosan-porous carbon nanomaterial and quaternary ammonium salt modified bentonite is (100-300) mL: (1-5) g: (5-15) g;
[0017] The initiator is a persulfate; based on the total mass of the initiators used in the first polymerization reaction and the second polymerization reaction being 100%, the initiator used in the first polymerization reaction is 30% to 50% of the total mass of the initiators, and the initiator used in the second polymerization reaction is 50% to 70% of the total mass of the initiators;
[0018] The ratio of the volume of the liquid polyaluminium chloride to the total mass of the initiator is (100-300) mL: (0.1-2) g.
[0019] Preferably, the temperature of the first polymerization reaction is 45-70°C, and the reaction time is 1-2h;
[0020] The temperature of the second polymerization reaction is 45-70° C., and the reaction time is 1-2 hours.
[0021] The present invention also provides a polymeric coagulant prepared by the preparation method described in the above scheme.
[0022] The present invention also provides the use of the polymeric coagulant described in the above scheme in water treatment.
[0023] The present invention provides a preparation method of a polymer coagulant, comprising the following steps: mixing liquid polyaluminium chloride, dimethyl diallyl ammonium chloride copolymer and part of an initiator to carry out a first polymerization reaction to obtain a reaction solution; mixing the reaction solution, chitosan-porous carbon nanomaterial, quaternary ammonium salt modified bentonite and the remaining part of the initiator to carry out a second polymerization reaction to obtain the polymer coagulant. The present invention uses liquid polyaluminium chloride, dimethyl diallyl ammonium chloride copolymer, chitosan-porous carbon nanomaterial and quaternary ammonium salt modified bentonite as raw materials to prepare a polymer coagulant, wherein the liquid polyaluminium chloride and dimethyl diallyl ammonium chloride copolymer can play the role of adsorption and electrical neutralization, adsorption bridging, and mesh cloth sweeping, the quaternary ammonium salt modified bentonite and chitosan-porous carbon nanomaterial have an adsorption effect, and the four raw materials are polymerized together to play a coagulation and adsorption effect, thereby achieving the purpose of efficiently removing organic pollutants and suspended matter. The results of the embodiment show that the polymer coagulant of the present invention is suitable for the treatment of various wastewaters such as muddy water, landfill leachate and domestic sewage, and the COD and suspended matter removal rates are both high. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing a polymeric coagulant, comprising the following steps:
[0025] Mixing liquid polyaluminium chloride, dimethyldiallylammonium chloride copolymer and part of initiator to carry out a first polymerization reaction to obtain a reaction liquid;
[0026] The reaction solution, chitosan-porous carbon nanomaterial, quaternary ammonium salt-modified bentonite and the remaining part of the initiator are mixed to carry out a second polymerization reaction to obtain the polymerization coagulant.
[0027] The present invention mixes liquid polyaluminium chloride and dimethyldiallyl ammonium chloride copolymer and part of the initiator to carry out a first polymerization reaction to obtain a reaction solution. In the present invention, the amount ratio of the liquid polyaluminium chloride and the dimethyldiallyl ammonium chloride copolymer is preferably (100-300) mL: (2-10) g, more preferably (150-250) mL: (3-8) g; the liquid polyaluminium chloride, the dimethyldiallyl ammonium chloride copolymer and part of the initiator are preferably stirred and mixed for 30-60 min, and then heated to react, and the stirring and mixing speed is preferably 100-500 r / min; the temperature of the first polymerization reaction is preferably 45-70° C., more preferably 50-60° C., and the reaction time is preferably 1-2 h; after the first polymerization reaction is completed, the obtained reaction solution is directly subjected to subsequent reactions without any treatment.
[0028] After the first polymerization reaction is completed, the present invention mixes the obtained reaction solution, chitosan-porous carbon nanomaterial, quaternary ammonium salt modified bentonite and the remaining part of the initiator to carry out a second polymerization reaction to obtain the polymerization coagulant. In the present invention, the preparation method of the chitosan-porous carbon nanomaterial preferably includes the following steps: mixing chitosan, porous carbon, water and alkaline reagent for composite reaction to obtain the chitosan-porous carbon nanomaterial; the porous carbon is biological porous carbon, the porosity of the porous carbon is preferably 30-90%, and the specific surface area is preferably 100-2000m 2 / g; the mass ratio of chitosan to porous carbon is preferably 1:(1-3), specifically 1:1, 1:2 or 1:3; the alkaline reagent is preferably ammonia water, the mass fraction of the ammonia water is preferably 15%-40%, specifically 20%, 30% or 35%, and the amount of ammonia water is such that the reaction system reaches the required pH value for the composite reaction; the pH value of the composite reaction is preferably 8-9; the temperature of the composite reaction is preferably 60-80°C, specifically 65°C, 70°C or 75°C, and the reaction time of the composite reaction is preferably 1-2h; the composite reaction is preferably carried out under stirring conditions, and the stirring speed is preferably 2000-4000r / min.
[0029] In a specific embodiment of the present invention, chitosan and porous carbon are preferably first added to water and stirred until completely dissolved, then the temperature is raised to 60-80°C, and then ammonia water is slowly added to make the system reach the desired pH value, and then a composite reaction is carried out under heat preservation and stirring conditions. After the composite reaction is completed, the present invention preferably separates the obtained product, washes it to neutrality, and then dries it to obtain the chitosan-porous carbon nanomaterial.
[0030] In the present invention, the preparation method of the quaternary ammonium salt modified bentonite preferably comprises the following steps: mixing a quaternary ammonium salt solution and bentonite and then drying to obtain the quaternary ammonium salt modified bentonite. In the present invention, the concentration of the quaternary ammonium salt solution is preferably 1wt% to 7wt%, more preferably 3wt% to 5wt%; the dosage ratio of the quaternary ammonium salt solution to bentonite is preferably (2 to 6) mL: (1 to 2) g, more preferably (3 to 5) mL: (1.5 to 2) g; the quaternary ammonium salt in the quaternary ammonium salt solution is preferably a long-chain alkyl ammonium bromide; the number of carbon atoms of the long-chain alkyl in the long-chain alkyl ammonium bromide is preferably 16; specifically, the long-chain alkyl ammonium bromide preferably includes hexadecyltrimethylammonium bromide (CTMAB), ... One or more of alkyl trimethyl ammonium bromide, hexadecyl triethyl ammonium bromide and hexadecyl tributyl ammonium bromide, more preferably hexadecyl trimethyl ammonium bromide; the mixing temperature is preferably 45 to 70°C, more preferably 50 to 65°C, and the mixing is preferably carried out under water bath conditions; the mixing time is preferably 1 to 2 hours; the drying temperature is preferably 100 to 120°C; after drying, the present invention preferably grinds the dried product and sieves it to obtain the quaternary ammonium salt modified bentonite; the mesh number of the sieve for sieving is preferably 200 meshes. The present invention uses quaternary ammonium salt to modify bentonite, which can improve the adsorption performance of bentonite.
[0031] In the present invention, the dosage ratio of the liquid polyaluminium chloride, chitosan-porous carbon nanomaterial and quaternary ammonium salt modified bentonite is preferably (100-300) mL: (1-5) g: (5-15) g, more preferably (150-250) mL: (2-4) g: (8-12) g; the initiator is preferably persulfate, and the persulfate preferably includes one or more of ammonium persulfate, potassium persulfate and sodium persulfate; based on the total mass of the initiators used in the first polymerization reaction and the second polymerization reaction as 100%, the initiator used in the first polymerization reaction is 30%-50% of the total mass of the initiators, and the initiator used in the second polymerization reaction is 50%-70% of the total mass of the initiators; the ratio of the volume of the liquid polyaluminium chloride to the total mass of the initiators is (100-300) mL: (0.1-2) g; the persulfate is preferably used in the form of a persulfate solution, and the concentration of the persulfate solution is preferably 0.1-0.5 g / mL.
[0032] In the present invention, the temperature of the second polymerization reaction is preferably 45-70° C., and the reaction time is 1-2 hours. In a specific embodiment of the present invention, after the first polymerization reaction is completed, chitosan-porous carbon nanomaterials, quaternary ammonium salt-modified bentonite and the remaining initiator are directly added.
[0033] The present invention also provides a polymeric coagulant prepared by the preparation method described in the above scheme.
[0034] The present invention also provides the application of the polymeric coagulant described in the above scheme in water treatment. In the present invention, the application specifically includes: adding the polymeric coagulant to sewage for coagulation; the COD value of the sewage is 100-12000 mg / L, and the content of suspended matter is 10-10000 mg / L; in a specific embodiment of the present invention, the sewage can be muddy water from a water plant, anaerobic effluent from landfill leachate, or domestic sewage; the addition amount of the polymeric coagulant is preferably 100-5000 mg / L; in a specific embodiment of the present invention, the addition amount of the coagulant is preferably determined according to the content of COD and suspended matter in the sewage.
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Preparation of hexadecyltrimethylammonium bromide modified bentonite: Take 200 mL of 5% hexadecyltrimethylammonium bromide solution, add 100 g of bentonite, mix evenly, place in a 60°C water bath for 1 hour, bake at 100°C until dry, grind and pass through a 200-mesh sieve to obtain hexadecyltrimethylammonium bromide modified bentonite.
[0038] Preparation of chitosan-porous carbon nanomaterials: Take 300 mL of pure water, add 10 g of chitosan and 10 g of bioporous carbon, stir at 200 r / min until completely dissolved, then heat to 60 ° C and slowly add 30 wt% ammonia water to make the pH value of the system reach 8. Continue heating, keep stirring at 200 r / min for 1 hour, wash to neutral, and dry for 10 hours to obtain chitosan-porous carbon nanomaterials.
[0039] Preparation of polymer coagulant: Take 200mL of liquid polyaluminium chloride, start stirring at a stirring speed of 300r / min, add 5g of dimethyldiallylammonium chloride copolymer, 1mL of ammonium persulfate solution with a concentration of 0.5g / mL, stir for 30min, heat to raise the temperature, react at 70°C for 1h, then add 3g of chitosan-porous carbon nanomaterial, add 10g of hexadecyltrimethylammonium bromide modified bentonite. Add 1mL of ammonium persulfate solution with a concentration of 0.5g / mL, react at 70°C for 1h, and obtain the polymer coagulant.
[0040] Example 2
[0041] Preparation of hexadecyltriethylammonium bromide modified bentonite: Take 100 mL of 3% hexadecyltriethylammonium bromide solution, add 50 g of bentonite, mix evenly, place in a 45°C water bath for 2 hours, bake at 120°C until dry, grind and pass through a 200-mesh sieve to obtain hexadecyltriethylammonium bromide modified bentonite.
[0042] Preparation of chitosan-porous carbon nanomaterials: Take 500mL of pure water, add 5g of chitosan and 10g of bioporous carbon, stir at 4000r / min until completely dissolved, then heat to 80°C and slowly add 40wt% ammonia water to make the pH value of the system reach 9. Continue heating, keep stirring at 300r / min for 2h, wash to neutrality, and dry for 10h to obtain chitosan-porous carbon nanomaterials.
[0043] Preparation of polymer coagulant: Take 300mL of liquid polyaluminium chloride, start stirring at a speed of 500r / min, add 10g of dimethyldiallylammonium chloride copolymer, 2mL of ammonium persulfate solution with a concentration of 0.3g / mL, stir for 60min, heat to raise the temperature, react at 60°C for 1h, add 5g of chitosan-porous carbon nanomaterial, add 8g of hexadecyltriethylammonium bromide-modified bentonite, 3mL of ammonium persulfate solution with a concentration of 0.3g / mL, react at 60°C for 1h, and obtain the polymer coagulant.
[0044] Example 3
[0045] Take 500mL of sludge water from a water plant, in which the COD content is 350mg / L and the suspended matter content is 300mg / L, add 100-500mg / L of the polymer coagulant prepared in Example 1, stir at 100r / min for 10min, stop stirring, take the supernatant to detect COD and suspended matter, and the results show that the COD and suspended matter removal rates are 70%-85% and 75%-90%, respectively.
[0046] Example 4
[0047] Take 500mL of anaerobic effluent from a certain landfill leachate, in which the COD content is 12000mg / L and the suspended matter content is 10000mg / L, add 1000-5000mg / L of the polymer coagulant prepared in Example 1, stir at 100r / min for 30min, stop stirring, take the supernatant to detect COD and suspended matter, and the results show that the COD and suspended matter removal rates are 40%-60% and 50%-70%, respectively.
[0048] Example 5
[0049] Take 500mL of domestic sewage, in which the COD content is 500mg / L and the suspended matter content is 300mg / L, add 100-500mg / L of the polymer coagulant prepared in Example 1, stir at 100r / min for 10min, stop stirring, take the supernatant to detect COD and suspended matter, and the results show that the COD and suspended matter removal rates are 60%-70% and 65%-75%, respectively.
[0050] In the manner of Examples 3 to 5, coagulation experiments were carried out using the polymeric coagulant prepared in Example 2. The results showed that both had high COD and suspended solids removal rates.
[0051] Comparative Example 1
[0052] Take 500mL of sludge water from a water plant (COD and suspended matter content are the same as in Example 3), add 100-500mg / L polyaluminium chloride, stir at 100r / min for 10min, stop stirring, take the supernatant to detect COD and suspended matter, the results show that COD and suspended matter removal rates are 30%-40% and 40%-60%, respectively.
[0053] Comparative Example 2
[0054] Take 500mL of anaerobic effluent from a certain landfill leachate (COD and suspended matter content are the same as in Example 4), add 1000-5000mg / L polyaluminium chloride, stir at 100r / min for 30min, stop stirring, take the supernatant to detect COD and suspended matter, the results show that the COD and suspended matter removal rates are 10%-30% and 30%-50%, respectively.
[0055] Comparative Example 3
[0056] Take 500mL of domestic sewage (COD and suspended matter content are the same as in Example 5), add 100-500mg / L polyaluminium chloride, stir at 100r / min for 10min, stop stirring, take the supernatant to detect COD and suspended matter, the results show that the COD and suspended matter removal rates are 20%-30% and 30%-50%, respectively.
[0057] According to the methods in Comparative Examples 1 to 3, experiments were conducted using polyferric chloride, and the results showed that the removal rates of COD and suspended solids in sewage were both low.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polymeric coagulant, characterized in that: The following steps are involved: Mixing liquid polyaluminium chloride, dimethyldiallylammonium chloride copolymer and part of initiator to conduct a first polymerization reaction to obtain a reaction liquid; The reaction solution, chitosan-porous carbon nanomaterial, quaternary ammonium salt-modified bentonite and the remaining part of the initiator are mixed to carry out a second polymerization reaction to obtain the polymerization coagulant.
2. The preparation method according to claim 1, characterized in that: The usage ratio of the liquid polyaluminium chloride and the dimethyldiallylammonium chloride copolymer is (100-300) mL: (2-10) g.
3. The preparation method according to claim 1, characterized in that: The preparation method of the chitosan-porous carbon nanomaterial comprises the following steps: mixing chitosan, porous carbon, water and an alkaline reagent for composite reaction to obtain the chitosan-porous carbon nanomaterial; The mass ratio of chitosan to porous carbon is 1:(1-3); the alkaline reagent is ammonia water, and the mass fraction of ammonia water is 15%-40%; the pH value of the composite reaction is 8-9; the temperature of the composite reaction is 60-80°C, and the reaction time is 1-2h.
4. The preparation method according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt modified bentonite comprises the following steps: mixing a quaternary ammonium salt solution and bentonite and then drying to obtain the quaternary ammonium salt modified bentonite; the mixing temperature is 45-70°C for 1-2 hours; and the drying temperature is 100-120°C.
5. The preparation method according to claim 4, characterized in that: The concentration of the quaternary ammonium salt solution is 1wt% to 7wt%; the dosage ratio of the quaternary ammonium salt solution to bentonite is (2-6)mL:(1-2)g; the quaternary ammonium salt in the quaternary ammonium salt solution is long-chain alkyl ammonium bromide; the number of carbon atoms of the long-chain alkyl in the long-chain alkyl ammonium bromide is 16.
6. The preparation method according to claim 5, characterized in that: The long-chain alkyl ammonium bromide includes one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium bromide, cetyltriethylammonium bromide and cetyltributylammonium bromide.
7. The preparation method according to claim 1, characterized in that: The usage ratio of the liquid polyaluminium chloride, chitosan-porous carbon nanomaterial and quaternary ammonium salt modified bentonite is (100-300) mL: (1-5) g: (5-15) g; The initiator is a persulfate; based on the total mass of the initiators used in the first polymerization reaction and the second polymerization reaction being 100%, the initiator used in the first polymerization reaction is 30% to 50% of the total mass of the initiators, and the initiator used in the second polymerization reaction is 50% to 70% of the total mass of the initiators; The ratio of the volume of the liquid polyaluminium chloride to the total mass of the initiator is (100-300) mL: (0.1-2) g.
8. The preparation method according to claim 1, characterized in that: The temperature of the first polymerization reaction is 45-70° C., and the reaction time is 1-2 hours; The temperature of the second polymerization reaction is 45-70° C., and the reaction time is 1-2 hours.
9. The polymeric coagulant prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the polymeric coagulant according to claim 9 in water treatment.
Citation Information
Patent Citations
Preparation method of composite coagulant
CN117209664A
Composite coagulant for landfill leachate treatment and preparation method thereof
CN118637726A
Powder flocculant for treating oily sewage on emergency accident site and preparation method of powder flocculant
CN119018995A
Cited By
Composite flocculant and application thereof
CN122254621A